SALURAN DISTRIBUSI BERAS DI KABUPATEN KLATEN - Arum Eka Nur Arifah, Dyah; Antriyandarti, Ernoiz (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
One of important aspects on food security is the distribution of rice. Klaten District is one of the rice producers in Central Java. Rice distribution channels exist in every area managed by government agencies, such as Agriculture, Food Security and Fisheries Office of Klaten District. This study aims to identify the distribution channels of rice and its constraints in Klaten District by using descriptive methods. The results showed that there were 5 rice distribution channels in Klaten District with the constraint of inefficiency of rice distribution channels from farmers to consumers, due to too many marketing agencies involved in the channels.